2023
DOI: 10.3390/jpm13050857
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Targeting of Pancreatic Cancer in the Liver with a Near-Infrared Anti-MUC5AC Probe in a PDOX Mouse Model: A Proof-of-Concept Study

Abstract: Accurately identifying metastatic disease is critical to directing the appropriate treatment in pancreatic cancer. Mucin 5AC is overexpressed in pancreatic cancer but absent in normal pancreas tissue. The present proof-of-concept study demonstrates the efficacy of an anti-mucin 5AC antibody conjugated to an IR800 dye (MUC5AC-IR800) to preferentially label a liver metastasis of pancreatic cancer (Panc Met) in a unique patient-derived orthotopic xenograft (PDOX) model. In orthotopic models, the mean tumor to bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…The efficacy of antibodies conjugated to NIR fluorophores to label and enhance the detection of breast, lung, pancreatic, prostate, and colorectal cancers have been demonstrated in preclinical mouse models. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several of these studies have now been translated to human trials, which have shown that the use of tumorspecific fluorescence labeling can detect additional residual tumor deposits or previously unrecognized synchronous disease in 14-50% of cases. [21][22][23][24][25] However, there are currently no FDA-approved agents for FGS of gastric cancer.…”
mentioning
confidence: 99%
“…The efficacy of antibodies conjugated to NIR fluorophores to label and enhance the detection of breast, lung, pancreatic, prostate, and colorectal cancers have been demonstrated in preclinical mouse models. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Several of these studies have now been translated to human trials, which have shown that the use of tumorspecific fluorescence labeling can detect additional residual tumor deposits or previously unrecognized synchronous disease in 14-50% of cases. [21][22][23][24][25] However, there are currently no FDA-approved agents for FGS of gastric cancer.…”
mentioning
confidence: 99%